ChemInform Abstract: Enantioselective Synthesis of Benzazepinoindoles Bearing Trifluoromethylated Quaternary Stereocenters Catalyzed by Chiral Spirocyclic Phosphoric Acids. Issue 49 (9th December 2014) - Li, Xuejian; Chen, Di; Gu, Haorui; Lin, Xufeng
Abstract 26 examples